Peningkatan Kuantitas dan Kualitas Produksi Kerupuk Basa di Desa Jegu, Kabupaten Tabanan - I Gusti Rai Agung Sugiartha; Arya Faisal Akbar; Made Agus Putra Subali (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
The partner in this program is the home industry of “basa” crackers or seasoning crackers. There are several partner problems, 1) Long production time, 2) Simple and conventional product packaging, 3) Profit sharing from product marketing. The solutions to overcome these problems are, 1) Providing production equipment, 2) Installing packaging label, 3) Promotion through facebook. The results are, 1) The partner is able to accelerate and increase production quantity where in single production, the partner can produce more than 105 packs of basa crackers. 2) Product quality is better with packaging label. 3) Promotion through facebook can expand market share.